School refusal as the first presentation of adverse childhood events and Autism Spectrum Disorder: A primary care case report - Siti Umi Fairuz Azmi Azmi; Zamrina Binti Amat Amat; Noor Azimah Binti Muhammad Muhammad; Wan Salwina Wan Ismail Wan Ismail (Journal of Clinical and Health Sciences, 2026)
School refusal has become an increasingly alarming issue post-pandemic, representing the emotional conflict manifested by a child refusing to attend school. This case study describes the management of a 13-year-old girl who presented to a primary care clinic with school refusal due to a history of adverse childhood events, leading to a diagnosis of mood disorder and newly suspected high-functioning autism. This report shares a unique interplay between school refusal, adverse childhood events, and psychological disorders. The patient's complex comorbidity required individualized case formulation, effective management through parental and teacher support, and a multidisciplinary intervention at the primary care clinic for favourable prognostic outcome.